The relative sensitivity of different mediterranean plant species to ozone exposure (Water, Air, & Soil Pollution, 1999)
An experimental study was performed in open-top chambers to assess the relative O3-sensitivity of the following Mediterranean woody plants: Quercus ilex ssp. ilex, Quercus ilex ssp. ballota, Olea europaea ssp. sylvestris, Ceratonia siliqua and Arbutus unedo. Assessment of O3 ‘sensitivity’ was based on the development of O3-induced visible injury and the extent of the reduction in relative growth rate induced by O3. Two-year-old seedlings were exposed in open-top chambers to charcoal filtered air (CFA), Non-filtered air (NFA) or Non-filtered air supplied with 40 ppb O3 from 09:00 to 18:00 hours (NFA+40). No clear relationships were found between the development of visible injury and effects on plant growth or accumulated biomass. Olea europea ssp. sylvestris and Quercus ilex ssp. ballota appeared to be the most O3-sensitive tree species screened; a ten month exposure to ambient O3 levels (AOT40 = 12.4 ppm.h) caused reductions in height and/or stem growth. Further research is needed to characterise the physiological, biochemical and anatomical characteristics that may underlie the ‘sensitivity’ of certain Mediterranean species to O3